Improvements in Attention and Cardiac Autonomic Modulation After a 2-Weeks Sprint Interval Training Program: A Fidelity Approach - de Sousa, Arilson F. M.; Medeiros, André R.; Benitez-Flores, Stefano; Del Rosso, Sebastián; Stults-Kolehmainen, Matthew; Boullosa, Daniel A. (Frontiers in Physiology, 2018)
This study aimed to: 1) investigate the influence of a 2-weeks sprint interval training (SIT) program on aerobic capacity, cardiac autonomic control and components of attention in young healthy university students; and 2) to ascertain whether training fidelity would influence these adaptations. One hundred and nine participants were divided into an experimental (EG) and control (CG) groups. The EG performed a SIT program that consisted of 6 sessions of 4 × 30 s “all-out” efforts on a cycle ergometer, interspersed with active rests of 4 min. The criterion for fidelity was achieving >90% of estimated maximum heart rate (HR) during sprint bouts. After analyses, the EG was divided into HIGH (n=26) and LOW (n=46) fidelity groups. Components of attention were assessed using the Attention Network Test (ANT). Aerobic capacity (VO2max) was estimated while the sum of skinfolds was determined. Autonomic control of HR was assessed by means of HR variability (HRV) and HR complexity at rest and during ANT. Both HIGH and LOW significantly increased aerobic capacity, vagal modulation before and during ANT, and executive control, and decreased body fatness after SIT (p<0.05). However, only participants from HIGH showed an increase in HR complexity and accuracy in ANT when compared to LOW (p<0.05). Two weeks of SIT improved executive control, body fatness, aerobic fitness and autonomic control in university students with better results reported in those individuals who exhibited high fidelity.